Fast computation of computer-generated hologram using Xeon Phi coprocessor - Murano, Koki; Shimobaba, Tomoyoshi; Sugiyama, Atsushi; Takada, Naoki; Kakue, Takashi; Oikawa, Minoru; Ito, Tomoyoshi (Computer physics communications, 2014)
We report fast computation of computer-generated holograms (CGHs) using Xeon Phi coprocessors, which have massively x86-based processors on one chip, recently released by Intel. CGHs can generate arbitrary light wavefronts, and therefore, are promising technology for many applications: for example, three-dimensional displays, diffractive optical elements, and the generation of arbitrary beams. CGHs incur enormous computational cost. In this paper, we describe the implementations of several CGH generating algorithms on the Xeon Phi, and the comparisons in terms of the performance and the ease of programming between the Xeon Phi, a CPU and graphics processing unit (GPU). Program title: Xeon-Phi-CGH Catalogue identifier: AETM_v1_0 Program summary URL:http://cpc.cs.qub.ac.uk/summaries/AETM_v1_0.html Program obtainable from: CPC Program Library, Queen’s University, Belfast, N. Ireland Licensing provisions: Standard CPC licence, http://cpc.cs.qub.ac.uk/licence/licence.html No. of lines in distributed program, including test data, etc.: 26539 No. of bytes in distributed program, including test data, etc.: 6144291 Distribution format: tar.gz Programming language: C, C++. Computer: Intel Xeon Phi coprocessor. Operating system: Linux. Has the code been vectorised or parallelized?: Yes. CPU and many cores in Xeon Phi coprocessor. RAM: 256M bytes Classification: 6.1, 6.5, 18. External routines: Intel MKL Nature of problem: We describe how to program fast computation of computer-generated holograms (CGHs) and diffraction calculation using Xeon Phi coprocessors, released by Intel. We describe the implementations of several CGH generating algorithms on the Xeon Phi, and the comparisons in terms of the performance and the ease of programming between the Xeon Phi, a CPU and graphics processing unit (GPU). Solution method: FFT-based diffraction calculations, computer-generated-hologram by direct integration.